2020
DOI: 10.1002/alz.12220
|View full text |Cite
|
Sign up to set email alerts
|

ABCA7 and the altered lipidostasis hypothesis of Alzheimer's disease

Abstract: We propose the altered lipidostasis hypothesis of Alzheimer's disease (AD). It holds that vulnerable neurons of the entorhinal region generate a neurodegenerative lipid during normal function, adenosine triphosphate–binding cassette transporter subfamily A member 7 (ABCA7) protects from AD pathogenesis by removing it out of the cell, generation of the lipid increases with age, and the minimal amount of ABCA7 needed to dispose of the rising volumes of the lipid also increases with age. A survey of ABCA7 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 62 publications
2
44
0
Order By: Relevance
“…Interestingly, no ABCA7 mRNA signal was initially detected in total human brain samples but this result was later refuted by several groups demonstrating mRNA and protein expression of ABCA7 in human and murine samples of the different cell types present in the brain [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Therefore, it is now largely demonstrated that ABCA7 is expressed in neurons, astrocytes, microglia, endothelial cells of the blood–brain barrier (BBB), brain pericytes, not only in mice but also in humans ([ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]— , and , accessed on 31 December 2020).…”
Section: Abca7 Expression Pattern and Structurementioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, no ABCA7 mRNA signal was initially detected in total human brain samples but this result was later refuted by several groups demonstrating mRNA and protein expression of ABCA7 in human and murine samples of the different cell types present in the brain [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Therefore, it is now largely demonstrated that ABCA7 is expressed in neurons, astrocytes, microglia, endothelial cells of the blood–brain barrier (BBB), brain pericytes, not only in mice but also in humans ([ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]— , and , accessed on 31 December 2020).…”
Section: Abca7 Expression Pattern and Structurementioning
confidence: 99%
“…Abca7 is mainly expressed by neurons and microglia in human and mouse brains [ 23 , 80 , 81 , 82 ]. Both isoforms described in Section 2.2 are observed by western blots in brain samples of healthy donors and AD patients [ 25 ].…”
Section: Roles Of Abca7 In Brain Functioning and In Alzheimer’s Disease (Ad)mentioning
confidence: 99%
See 2 more Smart Citations
“…ABCA7 is highly expressed in the brain, predominantly in neurons and microglia ( Zhang et al, 2014 ). Reduced ABCA7 levels are observed in AD brain ( Lyssenko and Praticò, 2020 ) and hippocampus of mice on a high fat diet ( Zou et al, 2020 ). Contrary to ABCA1, transcription of ABCA7 is downregulated when cholesterol levels are high in the cell ( Iwamoto et al, 2006 ).…”
Section: Dysregulation Of Brain Cholesterol In Ad; It Is In the Genesmentioning
confidence: 99%